Facile regiodivergent synthesis of spiro pyrrole-substituted pseudothiohydantoins and thiohydantoins via reaction of [e]-fused 1H-pyrrole-2,3-diones with thiourea - Kobelev, Aleksandr I.; Tretyakov, Nikita A.; Stepanova, Ekaterina E.; Dmitriev, Maksim V.; Rubin, Michael; Maslivets, Andrey N. (Beilstein Journal of Organic Chemistry, 2019)
A highly divergent synthesis of regioisomeric thiohydantoins and pseudothiohydantoins spiro-fused to a pharmacologically valuable pyrrole-2-one fragment involving the reaction of [e]-fused 1H-pyrrole-2,3-diones with thioureas was developed. The obtained spiro pseudothiohydantoin derivatives were found to undergo a pseudothiohydantoin–thiohydantoin rearrangement. The reactions were shown to proceed under catalyst-free conditions in good yields, and the products were isolated without applying preparative chromatography methods.
Keywords: diversity-oriented synthesis; hydantoin; nitrogen heterocycles; rearrangement; thiourea

(untitled) - Konnert, L.; Lamaty, F.; Martinez, J.; Colacino, E. (Chem. Rev., 2017)

World Health Organization Model List of Essential Medicines, 21st List (World Health Organization, 2019)

(untitled) - Krause, T.; Gerbershagen, M. U.; Fiege, M.; Weißhorn, R.; Wappler, F. (Anaesthesia, 2004)

(untitled) - Cereghino, J. J.; Brock, J. T.; Van Meter, J. C.; Kiffin Penry, J.; Smith, L. D.; Fisher, P.; Ellenberg, J. (Clin. Pharmacol. Ther. (Hoboken, NJ, U. S.), 1974)

(untitled) - Bianchini, D.; Lorente, D.; Rodriguez-Vida, A.; Omlin, A.; Pezaro, C.; Ferraldeschi, R.; Zivi, A.; Attard, G.; Chowdhury, S.; de Bono, J. S. (Eur. J. Cancer, 2014)

(untitled) - Baell, J. B.; Holloway, G. A. (J. Med. Chem., 2010)

(untitled) - Mendgen, T.; Steuer, C.; Klein, C. D. (J. Med. Chem., 2012)

(untitled) - Ulrich, H.; Sayigh, A. A. R. (J. Org. Chem., 1965)

(untitled) - Schaumann, E.; Grabley, S. (Justus Liebigs Ann. Chem., 1978)

(untitled) - Yamagishi, M.; Ozaki, K.-i.; Yamada, Y.; Da-Te, T.; Okamura, K.; Suzuki, M. (Chem. Pharm. Bull., 1991)

(untitled) - El-Aasar, N. K.; Saied, K. F. (J. Heterocycl. Chem., 2008)

(untitled) - Makarenko, A. G.; Parkhomenko, P. I.; Rozhenko, A. B.; Grigor'ev, A. A.; Rybakova, M. V.; Bezuglyi, Y. V. (Chem. Heterocycl. Compd., 1994)

(untitled) - Fathalla, W. M.; Pazdera, P. (Molecules, 2002)

(untitled) - Briel, D.; Aurich, R.; Egerland, U.; Unverferth, K. (Pharmazie, 2005)

(untitled) - Hilmy, K. M. H.; Soliman, D. H.; Shahin, E. B. A.; El-Deeb, H. S.; El-Kousy, S. M. (Eur. J. Med. Chem., 2014)

(untitled) - Belikov, M. Y.; Fedoseev, S. V.; Ievlev, M. Y.; Ershov, O. V. (Chem. Heterocycl. Compd., 2017)

(untitled) - Marson, C. M. (Chem. Soc. Rev., 2011)

(untitled) - Zheng, Y.; Tice, C. M.; Singh, S. B. (Bioorg. Med. Chem. Lett., 2014)

(untitled) - Lovering, F. (MedChemComm, 2013)

(untitled) - Sauer, W. H. B.; Schwarz, M. K. (J. Chem. Inf. Comput. Sci., 2003)

(untitled) - Aldeghi, M.; Malhotra, S.; Selwood, D. L.; Chan, A. W. E. (Chem. Biol. Drug Des., 2014)

(untitled) - Mohammad, H. B.; Khurshid, A.; Sudeep, R.; Jalaluddin, M. A.; Mohd, A.; Mohammad, H. S.; Saif, K.; Mohammad, A. K.; Ivo, P.; Inho, C. (Curr. Pharm. Des., 2016)

(untitled) - Hung, A. W.; Ramek, A.; Wang, Y.; Kaya, T.; Wilson, J. A.; Clemons, P. A.; Young, D. W. (Proc. Natl. Acad. Sci. U. S. A., 2011)

(untitled) - Murray, C. W.; Rees, D. C. (Angew. Chem., Int. Ed., 2016)

(untitled) - Stepanova, E. E.; Kasatkina, S. O.; Dmitriev, M. V.; Maslivets, A. N. (Synthesis, 2018)

(untitled) - Kobelev, A. I.; Stepanova, E. E.; Dmitriev, M. V.; Maslivets, A. N. (Beilstein J. Org. Chem., 2019)
10.3762/bjoc.15.32.

(untitled) - Kasatkina, S.; Stepanova, E.; Dmitriev, M.; Mokrushin, I.; Maslivets, A. (Tetrahedron Lett., 2019)

(untitled) - Konovalova, V. V.; Shklyaev, Y. V.; Maslivets, A. N. (ARKIVOC (Gainesville, FL, U. S.), 2015)

(untitled) - Konovalova, V. V.; Maslivets, A. N. (Mini-Rev. Org. Chem., 2019)

(untitled) - Mashevskaya, I. V.; Kol'tsova, S. V.; Voronina, E. V.; Odegova, T. F.; Maslivets, A. N. (Pharm. Chem. J., 2001)

(untitled) - Babenysheva, A. V.; Maslivets, V. A.; Maslivets, A. N. (Russ. J. Org. Chem., 2007)

(untitled) - Kobelev, A. I.; Stepanova, E. E.; Dmitriev, M. V.; Denislamova, E. S.; Maslivets, A. N. (Russ. J. Org. Chem., 2018)